DmS-Modeler: A tool for modeling decision-making systems for self-adaptive software domain - Affonso, Frank José [UNESP]; Leite, Gustavo [UNESP]; Nakagawa, Elisa Yumi (KSI Research, 2016)
The ability to modify its own structure and/or behavior at runtime is a native feature in the development of Self-adaptive Software (SaS). In previous work, a Reference Architecture for SaS (RA4SaS), an automated process for adaptation, and a framework for decision-making were developed to assist the development of SaS. Although such initiatives have collaborated with evolution of SaS, the design of the Decisionmaking Systems (DmS), element of first class for SaS, is manually conducted. Therefore, this paper presents a tool called DmSModeler, which aims to assist the development of DmS for SaS, providing facilities for modeling, calibration of such system, and automatic generation of infrastructure (i.e., source code and databases). Aiming to present the applicability of our tool, a case study was conducted and the results enable us to have good perspectives of contribution to the SaS area and other domains of software systems.
Keywords: Decision-making system; Reference architecture; Self-adaptive software; Tool